2019
DOI: 10.1101/579292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recombinant spider silk protein matrices facilitate multi-analysis of calcium-signaling in neural stem cell-derived AMPA-responsive neurons

Abstract: Short title: Neuronal differentiation of neural stem cells in 3D spider silk matrices Abbreviations: NSCs (neural stem cells), BMP4 (Bone Morphogenic protein 4), TuJ1 (Neuronal class III B-tubulin), P (poly-ornithine), F (fibronectin), ECM (extracellular matrix), 3D (three dimensional), BW (BMP4+Wnt3a) 2 Neural progenitors or stem cells (NSCs) show great promise in drug discovery and clinical application. Yet few efforts have been made to optimize biocompatible materials for such cells to be expanded and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Results revealed that cells cultured on spider silk surfaces were capable of differentiating into neuronal and astrocytic Molecules 2020, 25, 737 15 of 20 cells without any significant differences to cells cultured on polystyrene plates with fibronectin coatings. Lewicka et al [89] also showed that the 3D porous foam structure made of 4RepCT supported NSC attachment, survival and differentiation into astrocytes in 3D. In this study, they cultured NSCs isolated from the cerebral cortices of rat embryos on 3D foams and monitored the interaction of the cells within the porous structure in terms of generation of functional excitatory neurons from NSCs without the addition of animal or human-derived components.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 79%
See 2 more Smart Citations
“…Results revealed that cells cultured on spider silk surfaces were capable of differentiating into neuronal and astrocytic Molecules 2020, 25, 737 15 of 20 cells without any significant differences to cells cultured on polystyrene plates with fibronectin coatings. Lewicka et al [89] also showed that the 3D porous foam structure made of 4RepCT supported NSC attachment, survival and differentiation into astrocytes in 3D. In this study, they cultured NSCs isolated from the cerebral cortices of rat embryos on 3D foams and monitored the interaction of the cells within the porous structure in terms of generation of functional excitatory neurons from NSCs without the addition of animal or human-derived components.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 79%
“…Application of stem cells and neuronal progenitors in contact with recombinant spider silk was studied by Lewicka et al [89]. In general, this type of cells is capable of differentiating into neurons, astrocytes, and oligodendrocytes.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a recent study by Lewicka and co-workers reported that structures consisting of recombinant spidroins provide excellent matrices for the generation and analysis of stem cells and neuronal progenitors [71]. Moreover, DeSimone and colleagues have reported successful development of a hydrogel 'bioink' consisting of recombinant silk proteins encapsulating a…”
Section: Commercial Applications Of Recombinant Spider Silkmentioning
confidence: 99%
“…This work was funded by grants from CIMED, StratRegen (SFO to KI), Karolinska Institutets Forskningsstiftelser (2011FoBi023) (to AR), VR-MH (Project Grants to PU, AR, and OH), Karolinska Institutet (TEMA), the Swedish Childhood Cancer Foundation (BCF), the Swedish Cancer Society, and Vinnova (to OH). A previous version of this manuscript has been released as a pre-print at bioRxiv (Lewicka et al, 2019).…”
Section: Data Availability Statementmentioning
confidence: 99%